The 5th United Designs International Biennial Design Exhibition - Panayides, Angelos (My University, 2026)
1–17 July 2011, 50 – 1 Gallery Limassol, Cyprus. The 5th United Designs International Biennial Design ExhibitionThe 5th United Designs International Biennial Design Exhibition official visual identity and poster.Active Member of the organizing committee. Official Logo & visual identity Design. Promotion Poster Design. Poster Participation in the exhibition.